Psychopathology and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The psychopathology of childhood epilepsy was examined by comparing symptoms in 48 children with complex partial seizures (CPS), 39 with primary generalized epilepsy with absence (PGE), and 59 nonepileptic children, aged 5 to 16 years, referred by pediatric neurologists to the UCLA Department of Psychiatry and Neuropsychiatric Institute, Los Angeles, CA.